Associations of sitting time with leisure‐time physical inactivity, education, and body mass index change. (24th October 2019) - Piirtola, Maarit; Kaprio, Jaakko; Svedberg, Pia; Silventoinen, Karri; Ropponen, Annina
Abstract : We aimed to investigate the associations of long‐term leisure‐time physical inactivity, body mass index (BMI) change, and education with sitting time in a 35‐year follow‐up based on self‐reports in surveys. Influences of working status in 2011 and familial confounding on the associations were tested. Data were based on the population‐based Finnish Twin Cohort of 5232 twins (53‐67‐year‐old, 41% men) with four surveys in 1975‐2011. Statistical analyses were performed using linear regression with several covariates. The effect of familial confounding (genetics and shared environment) was analyzed using a co‐twin control design which should be interpreted as if familial confounding plays a role, an association should be seen among all individuals but not in discordant twin pairs. Compared to those not at work, those at work had a longer total sitting time/d. For those at work, higher education was associated with more total sitting but with less non‐work sitting. Long‐term leisure‐time physical inactivity was associated with more non‐work sitting among those at work, whereas long‐term weight gain with more total and non‐work sitting regardless of working status. Familial confounding attenuated the associations, except for the association of increasing BMI with total and non‐work sitting among women at work. To conclude, total sitting time was longer among those still at work, but it was also influenced by long‐term leisure‐time physical inactivity, higher education, and an increase of BMI over the years. Public health efforts should be targeted to reduce sedentary behavior by promoting life‐long leisure‐time physical activity and weight control.